Stablecoins as the Foundation of DeFi - Nguyen, Jan; Babušík, Martin; Škrabka, Jan; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
The aim of this thesis is to analyze the rapidly evolving stablecoin industry and to assess whether stablecoins can maintain their peg and function not only as the backbone of the DeFi ecosystem but also as a bridge to traditional finance. The thesis introduces the basic concepts of DeFi, explores the historical evolution, mechanisms, and regulatory frameworks of stablecoins, and examines their use cases both within DeFi and in real-world applications. The practical part provides a comparative analysis of the four largest stablecoins by market capitalization, evaluating their design, collateral models, and risks to better understand their position in the ecosystem.
Vedoucí práce: Martin Babušík
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: finance [obor dipl. práce]; diplomové práce; master's theses